RECONSTRUCTING PAST TEMPERATURE VARIATIONS: SOME METHODOLOGICAL ASPECTS - Dmitry Sonechkin; Bao Yang (Geography, Environment, Sustainability)
Three aspects essential for the paleoclimatic reconstructions are considered: calibration of proxy data on an example of tree-ring width records as the main source of proxy paleoclimatic information; taking into consideration an integral nonstationarity of multiscale climatic variations; and use of the empirical orthogonal function expansion for the goal of the past meteorological field reconstruction.